A prospective study of fatigue trajectories among in‐centre haemodialysis patients. Issue 1 (19th November 2019) - Picariello, Federica; Norton, Sam; Moss‐Morris, Rona; Macdougall, Iain C; Chilcot, Joseph
Abstract : Objectives: Fatigue is common and debilitating among dialysis patients. The aim of this study was to understand the longitudinal trajectory of fatigue and consider sociodemographic, clinical, and psychological factors that are related to variation in fatigue levels over time. Design: A prospective study of fatigue with yearly assessments over 3 years among prevalent in‐centre haemodialysis (HD) patients. Methods: Fatigue severity was measured using the Chalder Fatigue Questionnaire and fatigue‐related functional impairment using the Work and Social Adjustment Scale. The trajectories of fatigue outcomes were examined using piecewise growth models, using length of time on dialysis as time. Sociodemographic, clinical, and psychological predictors of fatigue were assessed using linear growth models, using follow‐up time. Results: One hundred and seventy‐four prevalent HD patients completed baseline measures, 118 at 12 months, 84 at 24 months, and 66 at 36 months. Fatigue severity scores decreased by 0.15 each year. Fatigue‐related functional impairment increased by 1.17 each year. In adjusted linear growth models, non‐white ethnicity was a significant predictor of lower initial fatigue severity ( B  = −2.95, 95% CI −5.51 to −0.40) and a greater reduction in fatigue severity of 1.60 each year (95% CI 0.35–2.36). A one‐point increase in damage beliefs was associated with a 0.36 increase in fatigue‐related functional impairment each year (95% CI −0.61 to −0.01). Conclusion: Damage beliefs predicted an increase in fatigue‐related functional impairment over time. However, the data strongly suggested that fatigue outcomes vary by length of time on dialysis. Statement of contribution What is already known on this subject? At least 1 in 2 haemodialysis (HD) patients are clinically fatigued. Growing evidence is available on the important role of psychological factors in fatigue across chronic conditions. The contribution of psychological factors, beyond distress, to fatigue in HD has not been examined to date. What does this study add? Ethnicity played a role in the initial level of fatigue severity and over time. Damage beliefs predicted an increase in fatigue‐related impairment over time. Data strongly suggested that fatigue outcomes vary by length of time on dialysis.